2019
DOI: 10.3389/fonc.2019.00183
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Insufficiency Fracture and Bone Metastasis After Radiotherapy in Patients With Cervical Cancer Detected by Bone Scan: Role of Magnetic Resonance Imaging

Abstract: Background: Insufficiency fracture (IF) can show increased uptake on a bone scan (BS). IFs are often misinterpreted as bone metastases if the characteristic “Honda sign” (H-sign) is invisible. The purpose of the present study was to evaluate the utility of magnetic resonance imaging (MRI) alone for the characterization of IF and bone metastasis after radiotherapy in patients with cervical cancer detected by BS. Materials and Methods: Our study included 40 patients with cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Meanwhile, 38.6% of ORNs and 19.4% of metastases that were not detected on BS were found on MRI, and the frequency of equivocal lesions was also reduced. These results were similar to those of several previous studies that assessed the added value of MRI or SPECT/CT to BS alone in the discrimination of RT-induced pelvic insufficiency fracture and pelvic metastasis in cervical cancer patients (13)(14)(15)22). Therefore, the results of our study indicated that MRI could be a noninvasive technique for further discrimination of new cervical spine lesions detected by BS.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Meanwhile, 38.6% of ORNs and 19.4% of metastases that were not detected on BS were found on MRI, and the frequency of equivocal lesions was also reduced. These results were similar to those of several previous studies that assessed the added value of MRI or SPECT/CT to BS alone in the discrimination of RT-induced pelvic insufficiency fracture and pelvic metastasis in cervical cancer patients (13)(14)(15)22). Therefore, the results of our study indicated that MRI could be a noninvasive technique for further discrimination of new cervical spine lesions detected by BS.…”
Section: Discussionsupporting
confidence: 91%
“…BS shows enough sensitivity for detecting metastasis, but it shows several limitations in specificity because many benign bone tumors, infections, and degenerative disease may also show abnormal radiotracer uptake (13,15,16,22). Recently, BS has been applied for detecting RT-induced bone complications and has shown variable sensitivity in the detection of insufficiency fractures after RT for pelvic malignancy, with a detection rate ranging from 40 to 87.5% (14,15,23). In this study, BS showed a detection sensitivity of 61.4% for detecting ORN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plain radiographs are not recommended as they can delay diagnosis due to difficulties caused by image interpretation [7]. Radiotherapy-induced IF and bone metastasis show an increased uptake on a bone scintigraphy after radiotherapy' but the typical 'H' sign of IF does not always appear, which can be misinterpreted as bone metastasis [8]; therefore, bone scintigraphy should not be the first choice.…”
Section: Discussionmentioning
confidence: 99%